De novo transcriptome dataset of a Mayorella species isolated from deep seaNCBI - Wenli Guo; Xiaoli Lei; Chen Liang; Jianming Chen (Data in Brief, 2025)
Mayorella marianaensis (Amoebozoa: Discosea) was the only Mayorella species isolated from deep sea (over 3000 m-depth). We firstly present a transcriptomic analysis of the non-model amoeba species collected from the Mariana Trench area. Illumina sequencing platform was used to generate data which including raw data, cleaned reads, de novo assembly, and functional annotation. After assembly, the final transcriptome consists of 57,459,544 transcripts with a mean length of 1646 and N50 length of 1170. The transcriptome has a completeness of 67.4 % as assessed by BUSCO. Functional annotation pathways related to signal transduction, transport and catabolism, and translation are the most annotated in the transcriptome.